Hibernoma of the Upper Extremity: Complete Case of a Rare but Benign Soft Tissue Tumor - Thomas Reichel; Kilian Rueckl; Annabel Fenwick; Niklas Vogt; Maximilian Rudert; Piet Plumhoff (Case Reports in Orthopedics)
Hibernoma is a rare benign lipomatous tumor showing differentiation of brown fatty tissue. To the author’s best knowledge, there is no known case of malignant transformation or metastasis. Due to their slow, noninfiltrating growth hibernomas are often an incidental finding in the third or fourth decade of life. The vast majority are located in the thigh, neck, and periscapular region. A diagnostic workup includes ultrasound and contrast-enhanced MRI. Differential diagnosis is benign lipoma, well-differentiated liposarcoma, and rhabdomyoma. An incisional biopsy followed by marginal resection of the tumor is the standard of care, and recurrence after complete resection is not reported. The current paper presents diagnostic and intraoperative findings of a hibernoma of the upper arm and reviews similar reports in the current literature.